2004
DOI: 10.1002/mnfr.200400052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roasting history and buffer composition on peanut protein extraction efficiency

Abstract: Peanut is a major allergenic food. Undeclared peanut (allergens) from mis-formulation or contamination during food processing pose a potential risk for sensitized individuals and must be avoided. Reliable detection and quantification methods for food allergens are necessary in order to ensure compliance with food labelling and to improve consumer protection. The extraction of proteins from allergenic foods and complex food products is an important step in any allergen detection method. In this study, the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 14 publications
6
66
0
1
Order By: Relevance
“…Here, we observed that increasing the pH of Tris·Cl bu er to 8, higher protein recoveries were obtained, speci cally 51% and 36% for raw and roasted peanuts, respectively. is evidence was also suggested by previous studies on processed peanuts, which confirmed that extraction solutions with pH ≥ 8.5 improved the protein recovery [18,26,27]. Besides the good observed results by Tris·Cl buffer for protein extraction of raw and treated peanuts, best recovery values were obtained with urea-TBS buffer.…”
Section: Bu Er Extraction E Ciency For Raw and Roasted Peanuts And Hasupporting
confidence: 79%
See 1 more Smart Citation
“…Here, we observed that increasing the pH of Tris·Cl bu er to 8, higher protein recoveries were obtained, speci cally 51% and 36% for raw and roasted peanuts, respectively. is evidence was also suggested by previous studies on processed peanuts, which confirmed that extraction solutions with pH ≥ 8.5 improved the protein recovery [18,26,27]. Besides the good observed results by Tris·Cl buffer for protein extraction of raw and treated peanuts, best recovery values were obtained with urea-TBS buffer.…”
Section: Bu Er Extraction E Ciency For Raw and Roasted Peanuts And Hasupporting
confidence: 79%
“…ese processing methods may induce protein modification, altering its intrinsic allergenicity through protein aggregation via disulfides or other interchain covalent bonds; all structural changes at the protein level may induce a concomitant disappearance or appearance of new IgE-binding epitopes [10][11][12]. Several authors reported that the thermal treatment causes changes in the structure/conformation of proteins in different matrix [13][14][15], depending on the structural and chemical properties of the protein itself, the type of thermal processing and the operating conditions applied (temperature, pH, and time) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to A. simplex protein, the extractability and ELISA-detectability appeared to be greatly dependent on the pH-values of the buffers. Measurable A. simplex proteins were only obtained under basic conditions, which is congruent to an observation made for other allergens in a previous study [43]. The Tris-glycine extraction buffer was found to be optimal considering the yield of detectable A. simplex proteins from thermally treated samples.…”
Section: Discussionsupporting
confidence: 88%
“…Protein solubilization and the modification of epitope configuration resulting from processing are challenges that need to be addressed during the development of immunoassays for processed foods. The solubilization of the target protein is a requirement to obtain successful immunoassay results [85,86]. Figure 16.4 shows solubility issues arising from a typical sample preparation prior to ELISA analysis.…”
Section: Improved Detection Methods For Processed Foodmentioning
confidence: 99%